Pseudo-symplectic methods for stochastic Hamiltonian systems - Anton, Cristina (My University, 2018)
We propose a systematic approach to construct explicit pseudo-symplectic schemes for stochastic Hamiltonian systems. This method is based on generating functions, so it is an extension of the techniques used for constructing high-order symplectic schemes for stochastic Hamiltonian systems. We study the order of convergence of the proposed explicit pseudo-symplectic schemes. The excellent long term performance of the pseudo-symplectic schemes is verified numerically.